Methods study on Ferrocoat Industries, Inc. - Dela Vega, Geraldine; Galarosa, Iris Ann; Mayoralgo, Ma. Anna Belen; Pira, Ma. Cristina; Senar, Racquel (College of Engineering, 1991)
This paper contains a comprehensive study of the methods and operations employed by Ferrocoat Industries, Inc., a company engaged in the powder coating of metal products. This begins with a documentation of the general processes, correspondingly aided by flow process charts of man, material and equipment types. A detailed presentation of the general processes follows to aid the reader visualize the activities of the plant. The presentation of existing operations is followed by a careful analysis in which the minute details, delays and flaws are examined. With the examination at hand, alternatives are presented prior to the statements of recommendations. Areas subject to improvement are enumerated. Based on some criteria mentioned in the succeeding page, recommendation is formulated with a final schedule for implementation accompanying the recommendation statement.